The Future Role of Smart Devices in Systems of Urban Concentrated Loading Areas - Krisztián Bóna; Dávid Lajos Sárdi; Aletta Büki; Viktória Domaniczki (Engineering Proceedings)
In innovative city logistics systems, there are three main node types: consolidation centers, cross-docks, and concentrated loading areas. Since the latter has an essential role in the future urban freight transport, and they are significant parts of today’s urban supply systems, logistics research must deal with them. In this paper, the role of smart devices in the future organization of loading areas is presented. First, previous related research results are examined, focusing on the current situation of concentrated loading areas, primarily in Budapest. Then, some relevant international solutions are shown, and after that, the integration possibilities of smart devices and the most important steps in introducing smart loading areas are summarized. At the end of the paper, some new city logistics concepts that apply them are outlined.